Saúde docente : uma realidade detectada - em direção ao bem-estar e a realização profissional - Mendes, Aline Rocha (2011)
This quantitative and qualitative type research has the objective of identify and analyze the malaise and well-being condition of 30 Elementary School teachers of Porto Alegre Municipal Net of Education, through information of their health care licenses obtained from the Health Municipal Secretary, questionnaires of Self-image and Self-Esteem, Self-actualization and the evaluation of the variables that are indicators of teacher‟s malaise/well-being, were answered, and analyzed with descriptive statistic, interview with five teachers using as a base the Teacher‟s malaise/well-being Research Interview Guide, analyzed through the Bardin‟s Content Analysis Technique, for a better understanding of the school‟s daily factors that influence the dynamics of teacher‟s malaise/well-being development. Supplemented with an Awareness Workshop to highlight the relationships in this school. While the licenses for health care verify that 35,4% of this school teachers requested this concession showing a high rate.For the answer‟s analysis is possible infer that the group seems to have a good Self-image and Self-Esteem, showing satisfaction for their life although they aim more professional success and improve their own health; indicate the partial unmet the physical needs and Self-actualization, respectively; demonstrate met more the needs of relationships and independency. In the malaise/well-being indicators and interviews analyses, was inferred that these educators are clearly about the elements that cause malaise and presented high rates of stress and exhaustion, but revealed believe that their work may help in a better society construction, which brings them well-being. In Final Comments is emphasized that several elements may contribute with the improvement of teacher‟s health and well-being conditions, for example, the school as a support and care environment, the positive interpersonal relationships and based in affection, actions by education systems and by health and social support.